Behind these four walls in love and in justice: an installation on space and memory on the urban poor community of Barangay Tatalon - Rivera, Amiel Louise M.; Imao, Abdulmari de Leon Jr.; Sta Ana, Mary Catherine P. (Quezon City College of Fine Arts, University of the Philippines Diliman, 2023)
Urban space has long been a subject of conflict, especially over ownership. Challenging social justice and equality in the eviction and displacement of the urban poor in the Philippines is one of the main issues being highlighted in this project. This thesis inquires about how I could translate the politics of space and memory in the urban poor community of Barangay Tatalon through an installation composed of found objects. It aimed to give a visual image of the plight of the urban poor, specifically of Barangay Tatalon, through the creation of an installation piece that depicts the politics of space and memory. The final work translates and includes personal accounts and images of the community from salvaged materials, thereby setting a conducive condition for the viewers to experience, empathize, and be involved in the work.
Thesis (Bachelor of Fine Arts in Sculpture)--University of the Philippines Diliman
Bibliography: unnumbered leaves 11-15
Keywords: Urban poor; Art installation; Demolition; Eviction